Full‐year in situ imaging reveals fine‐scale habitat differences among salp and doliolid life stages - Patrick I. Duffy; Laura M. Treible; Emily E. Gipson; Marc E. Frischer; Adam T. Greer (Limnology and Oceanography, 2026)
Doliolids and salps are pelagic tunicates that reproduce both asexually and sexually during their life history, occasionally forming massive blooms (> 1000 ind. m −3 ) that can clear large volumes of water daily. Although blooms of doliolids and salps are often associated with pulses of primary productivity, little is understood about their life history dynamics in response to the full range of oceanographic conditions they encounter. Here, we quantify patterns in the abundance and distribution of doliolid and salp life stages related to oceanographic variables using an in situ imaging vehicle deployed during monthly cruises from April 2021 to March 2022 in the South Atlantic Bight shelf. Doliolid life stages were observed across the mid‐shelf (25, 45 m isobaths) in all months in a variety of conditions, albeit often at low abundances ( −3 ), while salps were infrequently observed during winter months and were more common at the 45 m isobath. Relative to doliolids, salps were associated with a narrower range of shelf habitat conditions. A single parameter quotient analysis revealed doliolids associated with cooler temperatures (16–29°C), higher chlorophyll a (Chl a ) fluorescence (0.25–5 mg m −3 ), and more particles > 0.5 mm ESD (0–150 L −1 ) compared to salps (20–29°C, 0.25–2 mg m −3 Chl a , 0–70 particles L −1 ). For both taxa, sexual life stages were associated with smaller ranges of oceanographic variables compared to asexual stages, implying their population dynamics are influenced by sequences of conditions that may involve different water masses.

Late pregnancy is associated with an increase in regulatory cytokines and a decline in nematode-specific antibody levels in sheep infected with Teladorsagia circumcincta - Adam D. Hayward; Andrew W. Greer; David Frew; Margaret Oliver; Alison A. Morrison; Yvonne Bartley; Yolanda Corripio-Miyar; David J. Bartley; Fiona Kenyon; Mara Rocchi; Alasdair J. Nisbet; Tom N. McNeilly (Veterinary Parasitology, 2025)

Western Boundary Current–Subtropical Continental Shelf Interactions - William Savidge; Dana Savidge; Frederico Brandini; Adam Greer; Eileen Hofmann; Moninya Roughan; Ilson da Silveira; Iain Suthers (Oceanography, 2024)
Western boundary currents (WBCs) adjacent to subtropical continental shelves (STCSs; between ~25° and 35° latitude; Figure 1) transport heat, nutrients, and biota poleward along the western margins of major ocean basins, interacting with the continental margins and influencing their physics and biology. Eddies and meanders along the shelf edge upwell deep, nutrient-laden water that can be advected onto the adjacent shelves with a corresponding export of particle-rich shelf water (e.g., Lee et al., 1991; Kimura et al., 1997; Campos et al., 2000; Roughan and Middleton, 2002, 2004; Lutjeharms, 2006; Savidge and Savidge, 2014). Despite their similarities, the various STCS regions display key differences with respect to boundary current strength and variability, shelf width and geometry, and trophic structure. Comparative analyses of the physical forcing and biological responses among STCS have the potential to reveal common underlying properties, forcing mechanisms, and sensitivities to climatic perturbations that are not possible to elucidate with region-specific studies. This kind of fundamental understanding of relationships between physics and biological responses is critical to predicting consequences of environmental change across a wide range of spatiotemporal scales.

Environmental assessment of a novel ionic-liquid based method for recycling of PVC in composite materials - Marco Tomatis; Adam J. Greer; Kamil Oster; Aleksander Tedstone; Rosa M. Cuéllar-Franca; Arthur Garforth; Christopher Hardacre; Adisa Azapagic (Science of The Total Environment, 2023)

In situ imaging across ecosystems to resolve the fine‐scale oceanographic drivers of a globally significant planktonic grazer - Adam T. Greer; Moritz S. Schmid; Patrick I. Duffy; Kelly L. Robinson; Mark A. Genung; Jessica Y. Luo; Thelma Panaïotis; Christian Briseño‐Avena; Marc E. Frischer; Su Sponaugle; Robert K. Cowen (Limnology and Oceanography, 2023)
Doliolids are common gelatinous grazers in marine ecosystems around the world and likely influence carbon cycling due to their large population sizes with high growth and excretion rates. Aggregations or blooms of these organisms occur frequently, but they are difficult to measure or predict because doliolids are fragile, under sampled with conventional plankton nets, and can aggregate on fine spatial scales (1–10 m). Moreover, ecological studies typically target a single region or site that does not encompass the range of possible habitats favoring doliolid proliferation. To address these limitations, we combined in situ imaging data from six coastal ecosystems, including the Oregon shelf, northern California, southern California Bight, northern Gulf of Mexico, Straits of Florida, and Mediterranean Sea, to resolve and compare doliolid habitat associations during warm months when environmental gradients are strong and doliolid blooms are frequently documented. Higher ocean temperature was the strongest predictor of elevated doliolid abundances across ecosystems, with additional variance explained by chlorophyll a fluorescence and dissolved oxygen. For marginal seas with a wide range of productivity regimes, the nurse stage tended to comprise a higher proportion of the doliolids when total abundance was low. However, this pattern did not hold in ecosystems with persistent coastal upwelling. The doliolids tended to be most aggregated in oligotrophic systems (Mediterranea and southern California), suggesting that microhabitats within the water column favor proliferation on fine spatial scales. Similar comparative approaches can resolve the realized niche of fast‐reproducing marine animals, thus improving predictions for population‐level responses to changing oceanographic conditions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

High-Resolution Sampling of a Broad Marine Life Size Spectrum Reveals Differing Size- and Composition-Based Associations With Physical Oceanographic Structure - Adam T. Greer; John C. Lehrter; Benjamin M. Binder; Aditya R. Nayak; Ranjoy Barua; Ana E. Rice; Jonathan H. Cohen; Malcolm N. McFarland; Alexis Hagemeyer; Nicole D. Stockley; Kevin M. Boswell; Igor Shulman; et al. (Frontiers in Marine Science, 2020)
Observing multiple size classes of organisms, along with oceanographic properties and water mass origins, can improve our understanding of the drivers of aggregations, yet acquiring these measurements remains a fundamental challenge in biological oceanography. By deploying multiple biological sampling systems, from conventional bottle and net sampling to in situ imaging and acoustics, we describe the spatial patterns of different size classes of marine organisms (several microns to ∼10 cm) in relation to local and regional (m to km) physical oceanographic conditions on the Delaware continental shelf. The imaging and acoustic systems deployed included (in ascending order of target organism size) an imaging flow cytometer (CytoSense), a digital holographic imaging system (HOLOCAM), an In Situ Ichthyoplankton Imaging System (ISIIS, 2 cameras with different pixel resolutions), and multi-frequency acoustics (SIMRAD, 18 and 38 kHz). Spatial patterns generated by the different systems showed size-dependent aggregations and differing connections to horizontal and vertical salinity and temperature gradients that would not have been detected with traditional station-based sampling (∼9-km resolution). A direct comparison of the two ISIIS cameras showed composition and spatial patchiness changes that depended on the organism size, morphology, and camera pixel resolution. Large zooplankton near the surface, primarily composed of appendicularians and gelatinous organisms, tended to be more abundant offshore near the shelf break. This region was also associated with high phytoplankton biomass and higher overall organism abundances in the ISIIS, acoustics, and targeted net sampling. In contrast, the inshore region was dominated by hard-bodied zooplankton and had relatively low acoustic backscatter. The nets showed a community dominated by copepods, but they also showed high relative abundances of soft-bodied organisms in the offshore region where these organisms were quantified by the ISIIS. The HOLOCAM detected dense patches of ciliates that were too small to be captured in the nets or ISIIS imagery. This near-simultaneous deployment of different systems enables the description of the spatial patterns of different organism size classes, their spatial relation to potential prey and predators, and their association with specific oceanographic conditions. These datasets can also be used to evaluate the efficacy of sampling techniques, ultimately aiding in the design of efficient, hypothesis-driven sampling programs that incorporate these complementary technologies.

Contrasting fine‐scale distributional patterns of zooplankton driven by the formation of a diatom‐dominated thin layer - Adam T. Greer; Adam D. Boyette; Valerie J. Cruz; Mustafa Kemal Cambazoglu; Brian Dzwonkowski; Luciano M. Chiaverano; Steven L. Dykstra; Christian Briseño‐Avena; Robert K. Cowen; Jerry D. Wiggert (Limnology and Oceanography, 2020)
Although plankton thin layers have been described and modeled in a variety of environments, the physical structure surrounding the layer, associated biological rates, and distributions of multiple trophic levels are rarely examined simultaneously. Similar combinations of measurements, such as growth, mortality, and spatial relationships among plankton, are key to understanding how physical processes generating thin layers can influence abundances, composition, and predator‐prey interactions. An in situ imaging system was deployed along a southward‐oriented transect to describe the full ~ 2.3‐km extent of a thin layer arching from 8 to 4 m deep, with Chlorophyll a enhanced by an order of magnitude inside the layer (23.9 mg m −3 peak concentration). Physical oceanographic measurements, distributions of different plankton groups, and output from a high‐resolution model indicated that surface convergence and vertical shear drove the formation of the layer, which was dominated by Odontella sp. diatoms that were relatively scarce in the broader study region. Phytoplankton apparent growth (0.64 d −1 ) balanced microzooplankton grazing rates (0.52 d −1 ) within the layer, whereas grazing mortality (2.23 d −1 ) greatly exceeded phytoplankton growth (−0.39 d −1 ) outside the thin layer. Mesozooplankton had starkly differing distributions; copepods aggregated south of the layer near the surface, and doliolids followed the thin layer trajectory. A physical oceanographic model run over a 1‐month time period, including the time of sampling, indicated that similar surface convergences occurred frequently. Thin layers driven by convergence and shear may be common, with behavioral and buoyancy differences among plankton likely contributing to community structure and modification of trophic transfer.

Identification and QTL mapping of resistance to Turnip yellows virus (TuYV) in oilseed rape, Brassica napus - Dieter Hackenberg; Elvis Asare-Bediako; Adam Baker; Peter Walley; Carol Jenner; Shannon Greer; Lawrence Bramham; Jacqueline Batley; David Edwards; Regine Delourme; Guy Barker; Graham Teakle; et al. (Theoretical and Applied Genetics, 2020)
Key message Partially dominant resistance to Turnip yellows virus associated with one major QTL was identified in the natural allotetraploid oilseed rape cultivar Yudal. Abstract Turnip yellows virus (TuYV) is transmitted by the peach-potato aphid ( Myzus persicae ) and causes severe yield losses in commercial oilseed rape crops ( Brassica napus ). There is currently only one genetic resource for resistance to TuYV available in brassica, which was identified in the re-synthesised B. napus line ‘R54’. In our study, 27 mostly homozygous B. napus accessions, either doubled-haploid (DH) or inbred lines, representing a diverse subset of the B. napus genepool, were screened for TuYV resistance/susceptibility. Partial resistance to TuYV was identified in the Korean spring oilseed rape, B. napus variety Yudal, whilst the dwarf French winter oilseed rape line Darmor- bzh was susceptible. QTL mapping using the established Darmor- bzh × Yudal DH mapping population (DYDH) revealed one major QTL explaining 36% and 18% of the phenotypic variation in two independent experiments. A DYDH line was crossed to Yudal, and reciprocal backcross (BC 1 ) populations from the F 1 with either the susceptible or resistant parent revealed the dominant inheritance of the TuYV resistance. The QTL on ChrA04 was verified in the segregating BC 1 population. A second minor QTL on ChrC05 was identified in one of the two DYDH experiments, and it was not observed in the BC 1 population. The TuYV resistance QTL in ‘R54’ is within the QTL interval on Chr A04 of Yudal; however, the markers co-segregating with the ‘R54’ resistance are not conserved in Yudal, suggesting an independent origin of the TuYV resistances. This is the first report of the QTL mapping of TuYV resistance in natural B. napus .

Acoustic detection of zooplankton diel vertical migration behaviors on the northern Gulf of Mexico shelf - Sabrina M. Parra; Adam T. Greer; Jeffrey W. Book; Alison L. Deary; Inia M. Soto; Carla Culpepper; Frank J. Hernandez; Travis N. Miles (Limnology and Oceanography, 2019)
Zooplankton respond to light levels, oceanographic conditions, and other cues through diel vertical migrations (DVMs), which can occur at dawn and dusk. However, unraveling the influence of these drivers is difficult without high‐resolution time series data encompassing multiple events that can alter zooplankton DVM. We address this knowledge gap with an interseasonal study using high‐resolution measurements of zooplankton DVMs on the freshwater‐influenced northern Gulf of Mexico shelf. Sampling encompassed 6 months of acoustic backscatter and vertical velocity profiles at five locations, supplemented with zooplankton taxonomic composition and abundance from in situ imaging, net samples, glider profiles, and remote sensing. Relative backscatter anomalies (RBAs) displayed a daily pattern that changed abruptly at dawn and dusk, with lower daytime (2–15 dB lower) values relative to nighttime. Daily variability intensified from autumn to spring. The DVM pattern changed in structure on shorter temporal scales (days to weeks), associated with factors including onshore and off‐shelf currents, lunar variability, cloud cover, and harmful algal bloom passage. In situ imaging and net observations showed that the most likely acoustically observed migrating zooplankton were chaetognaths, shrimp (performing reverse DVMs), copepods, and ostracods. Shrimp and chaetognath orientations also showed diel variability, with individuals more frequently oriented vertically during the daytime. Daily RBA and vertical velocity anomaly patterns could be caused by reverse DVM to the near‐surface or nocturnal DVM to the near‐bottom (outside the acoustic detection range) or diel changes in organism orientation. Pattern complexities suggest that multiple behaviors are happening and being observed simultaneously.

Functioning of Coastal River-Dominated Ecosystems and Implications for Oil Spill Response: From Observations to Mechanisms and Models - Adam Greer; Alan Shiller; Eileen Hofmann; Jerry Wiggert; Sally Warner; Sabrina Parra; Chudong Pan; Jeffrey Book; DongJoo Joung; Steven Dykstra; Jeffrey Krause; Brian Dzwonkowski; et al. (Oceanography, 2018)

Associations between lobster phyllosoma and gelatinous zooplankton in relation to oceanographic properties in the northern Gulf of Mexico - Adam T. Greer; Christian Briseño‐Avena; Alison L. Deary; Robert K. Cowen; Frank J. Hernandez; William M. Graham (Fisheries Oceanography, 2017)
Lobster phyllosoma are known to associate with large cnidarian medusae; however, direct quantitative observations are difficult because gelatinous zooplankton are extremely fragile, and the phyllosoma easily detach from their host when sampled by plankton nets. We provide the first large scale quantitative information of the distribution of this association using an in situ imaging system, with synoptic measurements of water column properties. All phyllosoma were identified as slipper lobsters ( Scyllarus chacei ) and were associated with previously unreported “hosts” such as small hydromedusae, doliolids, and siphonophores in the northern Gulf of Mexico. Along the shelf, phyllosoma were more likely to be present at greater depths and higher salinities. Approximately 30% of the 347 lobster phyllosoma imaged were attached to at least one gelatinous organism, and salinity and depth were positively related to the probability of attachment on 30 October, but did not show a significant relationship for the other days of sampling. Many of the phyllosoma were larger than the gelatinous organisms to which they were attached, and some gelatinous zooplankton showed damage likely from feeding by the phyllosoma. In this coastal environment, gelatinous zooplankton tended to be more abundant in the same offshore region where phyllosoma occurred, so these gelatinous “hosts” may provide a steady food supply in the more oligotrophic waters on the outer shelf. Similar complex interactions among zooplankton may influence the life histories of other species, hindering our ability to forecast ecosystem level processes until the population level consequences of species interactions are fully understood.

Divergent functional traits in three sympatric Arctic charr Salvelinus alpinus morphs are not coupled with the age of the lineage divergence - Carolyn Bryce; Alicia Fraser; Rune Knudsen; Ron Greer; Colin Adams (Hydrobiologia, 2016)

Qualitative Assessment of Agritourism Safety Guidelines: A Demonstration Project - Robin Tutor-Marcom; Annette Greer; Maria Clay; Tammy Ellis; Tami Thompson; Esther Seisay Adam-Samura (Journal of Agromedicine, 2013)

Trophic polymorphism amongst Arctic charr from Loch Rannoch, Scotland - C. E. Adams; D. Fraser; F. A. Huntingford; R. B. Greer; C. M. Askew; A. F. Walker (Journal of Fish Biology, 1998)
This paper describes the results of a multivariate and univariate morphometric analysis of three groups of Arctic charr Salvelinus alpinus from Loch Rannoch, Perthshire, Scotland, distinguished a priori on the basis of coloration (bright v. cryptic) and site of capture (from two locations 12 km apart). The analysis produced a clear and highly significant distinction, not only between brightly and cryptically coloured charr, but also between the two cryptically coloured groups, one of which was more robust in terms of several size‐independent head measurements. Stomach analysis showed that the brightly coloured charr fed entirely on zooplankton, the less robust, cryptically coloured fish, fed on benthic macroinvertebrates, whereas a significant proportion of the diet of the more robust cryptically‐coloured form consisted of other fish. Differences in length at age also distinguished the three forms, with the robust, piscivorous charr, which live longer and potentially reach a larger final size, attaining smaller sizes at a given age. These data clearly confirm the previous identification of a distinct planktivorous morph of Arctic charr in Loch Rannoch and extend the morph analysis by distinguishing two additional morphs, a benthivorous morph and a piscivorous morph that are morphologically and ecologically distinct. The results are discussed in the context of other systems in which sympatric morphs of Arctic charr have been described.